13.26% Efficiency Polymer Solar Cells by Optimizing Photogenerated Exciton Distribution and Phase Separation with the Third Component. Issue 11 (1st August 2019) - Zhang, Miao; Zhang, Zhuohan; Wang, Jian; An, Qiaoshi; Peng, Hongshang; Tang, Weihua; Zhang, Fujun
Abstract : Ternary polymer solar cells (PSCs) are designed by incorporating varied PC71 BM into a PBDB‐T:INPIC‐Si‐based binary system. The PC71 BM incorporation can replenish weak absorption of PBDB‐T and INPIC‐Si in the short wavelength from 300 to 500 nm. Effective charge transport channels can be formed in ternary active layers due to good compatibility of the used materials. The optimized ternary PSCs exhibit a power conversion efficiency (PCE) of 13.26% with short‐circuit current density ( J SC ) of 20.98 mA cm −2, open‐circuit voltage of 0.892 V, and fill factor (FF) of 70.84%. The 13.26% PCE is among the top values for ternary PSCs with fullerene derivative and nonfullerene materials as acceptors. An approximately 12.5% PCE improvement is obtained compared with INPIC‐Si‐based binary PSCs, originating from simultaneously increased J SC and FF of the optimized ternary PSCs. The balanced photon harvesting is obtained in the whole wavelength range by regulating PC71 BM content in acceptors, leading to increased J SC of ternary PSCs. The molecular arrangement and phase separation are well optimized in ternary blend films, resulting in the enhanced FF of ternary PSCs. The photogenerated exciton distribution is optimized according to optical field distribution of ternary active layers, which further support the J SC and FF improvement. Abstract : Ternary polymer solar cells (PSCs) are fabricated with PBDB‐T:PC71 BM:INPIC‐Si as the active layers. The power conversion efficiency (PCE) reaches 13.26% for ternary PSCs with 20 wt% PC71 BM, which is larger than that for INPIC‐Si or PC71 BM‐based PSCs with PCEs of 11.79% or 6.26%. Light absorption, exciton distribution, and film morphology can be simultaneously optimized by incorporating appropriate PC71 BM.